O-028 Endovascular Treatment of Small-Unruptured Cerebral Aneurysms with Flow Diverters. (26th July 2014) - Piotin, M; Bartolini, B; Redjem, H; Pistocchi, S; Blanc, R
Abstract : Purpose: To assess the safety and efficacy issues of Flow Diverters (FD) in the treatment of small unruptured cerebral aneurysms. Methods: Retrospective review of a prospectively gathered database of endovascularly treated aneurysms since the introduction of FD. From September 2008 (when treatment aneurysms with FD was initiated at our institution) to January 2014, 519 small (<10 mm), unruptured aneurysms were treated by endovascular means. Four treatment modalities were individualised: simple coiling, balloon-assisted coiling, stent-assisted coiling and aneurysm neck coverage with FD. Results: (87/519) 16.8% (mean sac size: 5.0 mm, 70.1.4% bifurcation) of aneurysms were simply coiled. (189/519) 36.4% (mean sac size: 4.9 mm, 54.5% bifurcation) of aneurysms were coiled with balloon assistance. (166/519) 32.0% (mean sac size: 6.1 mm, 75.3% bifurcation) of aneurysms were coiled with stent-assistance. (77/519) 14.8% (mean sac size: 5.0 mm, 14.5% bifurcation) aneurysms were treated with FD. Procedural perioperative and delayed (up to 180 days) permanent neurological complications were 0.0%, 4.0%, 10.1% and 3.1% respectively, with a marked trend for more complications with stent-assisted coiling (P = 0.0037). Total immediate aneurysm occlusion was obtained in 49.4% (43/87), 53.4% (101/189), 59.0% (98/166) and 3.9% (3/77) respectively, with a marked trend toward better occlusion with stent-assisted coiling technique (P < 0.0001). At a mean angiographic follow-up of 16 months for aneurysms treated with FD and 23 months for the others, total aneurysm occlusion was 59.2% (32/54), 70.4% (88/125), 85.4% (111/130) and 70.7% (41/58) respectively, with a trend toward better occlusion with stent-assisted coiling (P = 0.0011). Conclusions: FD for the treatment of small-unruptured aneurysms confer a good safety profile that compares favorably with those of balloon-assisted technique, but are mostly indicated for sidewall aneurysms. Occlusion rates at follow-up are better with stent-assisted-coiling than FD but with higher morbidity. Disclosures: M. Piotin: 2; C; Covidien, Stryker, Balt, MicroVention, Reverse Medical, Neuravi, Penumbra. 4; C; Lazarus Effect. B. Bartolini: 2; C; Covidien, Stryker, Balt, MicroVention, Penumbra. H. Redjem: 2; C; Covidien, Stryker, Balt, MicroVention, Penumbra. S. Pistocchi: 2; C; Covidien, Stryker, Balt, MicroVention, Penumbra. R. Blanc: 2; C; Covidien, Stryker, Balt, MicroVention, Reverse Medical, Neuravi, Penumbra. 4; C; Lazarus Effect.